(untitled) (The Pakistan Development Review, 1994)
In order to curb the harmful effects of population growth many developing countries initiated family planning programmes around the year 1960. These programmes traditionally consisted of two components namely provision of family planning services on the supply side and Information, Education and Communication (lEe) on the demand side. In many of these countries the IEC component has been performing functions such as providing information about the locations and types of services available and motivating couples to adopt family plan,ning. Besides, IEC has also been performing the function of educating the local and national leaders and educated people about population problems and benefits of smaller family size [Rogers (n.d.)]. The channels through which IEC messages are conveyed are either mass media or interpersonal communication. Mass media includes television, radio, and print media. Planned interpersonal channels include person to person contacts by home visitors etc. Whereas unplanned interpersonal communication consists of exchanges between husband and wife, among relatives and friends.